An approach for applying artificial intelligence to smart-home - Nguyen , Tat Bao Thien; Truong , Tien Sy (Journal of Technical Education Science, 2020)
In recent years, along with the development of science and technology, especially the techniques of artificial intelligence has appeared in many areas of life in that smart-home is not an exception. The houses of which devices were controlled through the voice recognition has been the trend of smart-home development. In this article, we applied machine learning models to a smart-home with voice-controlled devices to enhance the accuracy and flexibility of the system (for example, when the operator says "control intents" which are similar to the programmed keywords, the control system still understands and executes). With the applications of machine learning models such as multi-layer neural networks and one-class support vector machine, we have already built a processing centre to classify data and make control decisions for smart-homes.